Application development: a strategic corporate innovation activity in the process industries. (16th March 2015) - Storm, Per; Lager, Thomas
In the process industries a substantial part of a supplying company's R&D lies in helping its customers' more effectively use the products it supplies, here denoted Application Development. Companies primarily carry out application development with near downstream customers in the supply/value chains. Almost all companies in this study also carried out application development with both customers' customers and customers' equipment suppliers. The results also indicate that application development resources are largely allocated to application areas and to customers of low to medium newness. A related matrix based on the dimensions of newness of the application area to the company, and newness of the customer to the company, proved to be an interesting tool in portfolio balancing. Because application development in the process industries has received little research attention so far, the findings from this study provide new insight into supplier–customer collaborative behaviour for the specific sub–topic of application development.